Long-term effects of the COVID-19 lockdown on the structural and functional outcomes of neovascular AMD patients in Suzhou, China - Zheyao Gu; Xiangying Luo; Ruizhu Sun; Ting Xi; Chunyuan Zhang (PLoS ONE, 2025)
Background Timely anti-vascular endothelial growth factor (VEGF) therapy is essential for visual function in neovascular age-related macular degeneration (nAMD). The coronavirus pandemic has led to unprecedented delays in anti-VEGF intravitreal therapy because of the need to reduce hospital attendance. Objectives To assess the long-term impact of COVID-19 pandemic-related delays in intravitreal anti-VEGF therapy on nAMD patients. Methods This was a retrospective study of 98 patients (102 eyes) with nAMD whose anti-VEGF treatments were interrupted for >  8 weeks due to the COVID-19 pandemic. Best-corrected visual acuity (BCVA), central retinal thickness (CRT) and anatomical characteristics on spectral domain optical coherence tomography (SD-OCT) were measured at baseline, at the last follow-up visit before treatment interruption (V0), at the first visit after the COVID-19 lockdown had ended (V1), at the six-month follow-up (V-6 months) and at the final visit at the 1-year follow-up (V-final). The control group included nAMD patients who had completed at least three anti-VEGF treatments and received consecutive follow-up with timely anti-VEGF treatments for one year. Results After one year of regular follow-up and standardized treatment, the treatment-interrupted group (TIG) had significantly worse visual acuity than the treatment-continuous group (TCG) (0.71 ± 0.38 vs. 0.52 ± 0.32, p < 0.001); however, there was no significant difference between the groups in the mean CRT (273.95 ± 112.96 µm vs. 261.43 ± 90.66 µm, p > 0.05). Furthermore, subgroup analysis revealed that, compared with those before treatment interruption, the BCVA of the TIG patients slightly improved, but the mean CRT and related activity indices returned to baseline values according to OCT imaging (all p > 0.05). Multiple linear regression analysis revealed that longer treatment interruption was associated with greater deterioration in visual acuity (p = 0.009). Conclusion Treatment interruption for more than 8 weeks had a sustained negative impact on visual acuity in treated eyes one year later. For nAMD patients, continuous treatment, regardless of the underlying regimen, remains critical.